2022 IEEE Global Engineering Education Conference (EDUCON) 2022
DOI: 10.1109/educon52537.2022.9766793
|View full text |Cite
|
Sign up to set email alerts
|

Impersonating Chatbots in a Code Review Exercise to Teach Software Engineering Best Practices

Abstract: Over the past decade, the use of chatbots for educational purposes has gained considerable traction. A similar trend has been observed in social coding platforms, where automated agents support software developers with tasks such as performing code reviews. While incorporating code reviews and social coding platforms into software engineering education has been found to be beneficial, challenges such as steep learning curves and privacy considerations are barriers to their adoption. Furthermore, no study has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…We found that genAI stimulated student engagement in the code review process, demonstrating a higher average number of identified issues compared to the peer review process and a higher average number of those issues identified by genAI were fixed. This aligns with results reported in previous studies that used automated peer feedback (Farah et al, 2022). Interestingly, inaccurate feedback and misunderstandings of project requirements encouraged students to revisit the inspected code and stimulated further critical discussion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that genAI stimulated student engagement in the code review process, demonstrating a higher average number of identified issues compared to the peer review process and a higher average number of those issues identified by genAI were fixed. This aligns with results reported in previous studies that used automated peer feedback (Farah et al, 2022). Interestingly, inaccurate feedback and misunderstandings of project requirements encouraged students to revisit the inspected code and stimulated further critical discussion.…”
Section: Discussionsupporting
confidence: 89%
“…By (partially) delegating code review responsibilities to AI-based tools, students can review and reflect on their coding practices without feeling exposed. Several previous studies investigated the use of automated code review in software engineering (Indriasari et al, 2020;Kaufmann et al, 2022;Farah et al, 2022), however, to the best of our knowledge, no previous work has investigated the use of generative AI combined with assessment checklists in educational code review processes.…”
Section: Code Review In Capstone Projectsmentioning
confidence: 99%
“…As chatbots have been particularly useful in computer-assisted language learning (CALL) [2,7,31], it would be particularly pertinent to implement chatbots aimed at supporting tasks in CALL (e.g., providing conversational practice, checking grammar, interfacing dictionaries). These implementations will be validated following experimental designs used in previous exploratory studies [11,12,14] comprising controlled experiments measuring learning gains, engagement, and usability using both standard (e.g., the User Experience Questionnaire [24] and the System Usability Scale [3]) and bespoke (e.g., scores calculated using the results of pre/post-tests) instruments. Third, the need to support instructors in the configuration and deployment of chatbots built with our blueprint was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have focused on the use of chatbots to support the code review process in formal education settings. We build on a previous Wizard of Oz [6] experiment [10] and a pilot study [8] to explore the impact that rule-based chatbots supporting code review exercises could have on the learning experience. In the following section, we present our guiding research question and the methodology we followed for our evaluation.…”
Section: Background and Related Workmentioning
confidence: 99%